The influence of customer experience, ease of use, trust, and customer satisfaction on repurchase intention of train tickets through the access by KAI application in Purwokerto City - Tiara Tiara; Ady Achadi; Enrico Aziezy (Privietlab, 2026)
This study aims to identify and analyze the influence of customer experience, ease of use, trust, and customer satisfaction on the repurchase intention of train tickets through the Access by KAI application in Purwokerto City. The population in this study is customers who purchased train tickets through Access by KAI in Purwokerto City, whose number is not known for certain. The sampling method used in this study is non-probability sampling with an accidental sampling technique. The minimum required sample size, according to Cochran's formula, is 97, and this study collected 100 respondents. Data analysis was conducted using multiple linear regression with IBM SPSS Statistics 22 software. The results of this study demonstrate that customer experience, ease of use, trust, and customer satisfaction significantly influence the repurchase intention of train tickets using the Access by KAI application in Purwokerto City.